Docstoc

Use the Product Rule to Simplify the Expression

Document Sample
Use the Product Rule to Simplify the Expression Powered By Docstoc
					    Use the Product Rule to Simplify the Expression
Use the Product Rule to Simplify the Expression

We use the product rule to simplify the expression where expression is a
combination of different kind of variables, numbers and operations like addition,
subtraction, multiplication and division.Now, we discuss how product rule
simplify different kind of expressions:

Combination of algebraic and exponential: If expression is a combination of
algebraic and exponential function, then with the help of product rule we can
easily solve differentiation of that expression-

 d (x.ex) = x. d (ex) + ex.d (x)
 dx             dx         dx
          = x.ex + ex.1
          = ex(x+1)
                                          Know More About Antiderivative of a x
 Combination of algebraic and trigonometric: If expression is a combination of
algebraic and trigonometric function, then-

  d (x2.sin x) = x2. d (sin x) + sinx.d (x2)
  dx                dx               dx
              = x2.(cos x) + sin x .(2x)
              = x(x.cos x + 2.sin x)

Combination of algebraic and logarithm: If expression is a combination of
algebraic and logarithm function, then-

   d (x.ln x) = x. d (ln x) + ln x.d (x)
   dx              dx              dx
              = x.(1) + ln x.(1)
                   x
              = 1+ ln x

Combination of trigonometric: If expression is a combination of two
trigonometric functions, then-

   d (sin x. cosx) = sin x. d (cos x) + cos x.d (sin x)


                                    Learn More About Antiderivative Trig Functions
          dx        dx           dx
          = sin x.(-sin2x) + cos x.(cos x)
          = cos2x – sin2x
          = cos2x

Combination of trigonometric and exponential: If expression is a combination of
trigonometric and exponential function, then-

   d (sin x.ex) = sin x. d (ex) + ex. d (sin x)
   dx                    dx         dx
                = sin x. (ex) + ex.(cos x)
             = ex (sinx + cos x)

These are different expressions which we simplify by product rule.
   Thank You




TutorCircle.com